Psychoanalytical Approach to Transnational Money Laundering Utilizing Japanese Mobile Online Games with Gacha System: A Forecasting Study - Rio Akbar Pramanta; Tri Cahyo Utomo (Journal of International Relations Diponegoro, 2019)
The problems to face money laundering acts are the methods which the criminals are usingthat keeps on changing and improving along with the development of modern technology.While law enforcement mostly trying to prevent it by tampering by the technology used, thereis a blind spot where there exists the reason of why and how the crime was possible in the firstplace. Some even neglected and underestimated by the authorities because of how the societyviews it in general, this is the recklessness the criminals can exploit. While money launderingutilizing Online Games, moreover with a Gacha system may sounds as bizarre as it is, it canbe done and this article is intended to explain the what, why, who, and how of it. Using theLacanian Psychoanalysis as a problem dissecting tool, the key here is to explain what makesthe condition and environment where such crime is possible, involving the Otaku Subculturepart of society in Japan and Indonesia, the companies behind it, and the Mobile Online Gamesitself. This article is forecasting the problems that will emerges concerning the crime of moneylaundering and its methods.